Analysis of chromosome number and speculations on the origin of Arundo donax L. (Giant Reed) - Bucci, A.; Cassani, E.; Landoni, M.; Cantaluppi, E.; Pilu, R. (Цитология и генетика, 2013)
Arundo donax (commonly called Giant Reed) is a perennial rhizomatous grass native to Asia, nowadays diffused all over the world. Due to its high biomass production and great adaptability to marginal land, interest in this species is increasing. In fact A. donax could represent an important and promising energy crop for heat and bioethanol second generation production. The propagation of A. donax is strictly agamic by rhizome fragmentation and cane node germination, strongly limiting the possibility of genetic improvement by breeding. The sterility could be caused by the fact that A. donax is a hybrid with uneven ploidy or a triploid species. It is difficult to propose an explanation for its sterility, because the chromosome number of A. donax is still a matter of debate, due to the high number and small size of the chromosomes; in the bibliography different counts ranging from 40 to 110 are reported. With the aim of establishing the chromosome number of A. donax we selected and counted 17 metaphase plates prepared from root tips obtained by hydroponic cultivation of cane nodes; our counts showed that A. donax most probably has 110 chromosomes. Our results suggested us two possible hypotheses, also based on SSR molecular marker results, concerning the evolutionary processes involved in the origins of A. Donax.